2017
DOI: 10.1002/ajim.22720
|View full text |Cite
|
Sign up to set email alerts
|

Non‐fatal agricultural injury surveillance in the United States: A review of national‐level survey‐based systems

Abstract: Improving data quality, timeliness and flexibility will provide reliable and valid injury estimates, and increase the usefulness of these surveys for surveillance and prevention of farm injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 37 publications
2
19
0
Order By: Relevance
“…Moreover, collecting injury data in this population through surveys that reach all workers, including self-employed and part-time producers, is wrought with challenges because of the lack of sufficient rosters for recruitment, a predictably low response rate, and all at a very high cost. Analyses of past survey surveillance programs unveiled other major gaps including data quality issues partly due to nonresponse, measurement errors and underreporting, untimeliness, and a lack of flexibility toward intersystem integrations [30].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, collecting injury data in this population through surveys that reach all workers, including self-employed and part-time producers, is wrought with challenges because of the lack of sufficient rosters for recruitment, a predictably low response rate, and all at a very high cost. Analyses of past survey surveillance programs unveiled other major gaps including data quality issues partly due to nonresponse, measurement errors and underreporting, untimeliness, and a lack of flexibility toward intersystem integrations [30].…”
Section: Introductionmentioning
confidence: 99%
“…Yurtlu et al (2012) investigated risk perceptions in operation of agricultural machinery, Güğercin et al (2016) assessed job safety and occupational health attitudes of agricultural engineers. Patel et al (2017) carried out a study in the USA and indicated that nonfatal agricultural injuries were mostly assessed through national surveys, data quality were most of the time insufficient, data were misleading and were not integrated into the current systems.…”
Section: Introductionmentioning
confidence: 99%
“…and agency reports, such as traffic accidents and insurance claims, including workers' compensation (Pinzke et al, 2018;Bonauto et al, 2003;Pate and Merryweather, 2012;Patel et al, 2017;Kim et al, 2018;VanWormer et al, 2017;Forst and Erskine, 2009;Scott et al, 2015Scott et al, , 2017Denning and Jennissen, 2018;Carnedas et al, 2018;Rautianien et al, 2005Rautianien et al, , 2009. Each method of data collection can provide information and insights needed for targeted intervention.…”
mentioning
confidence: 99%